Immunosenescence and inflammaging in Parkinson’s disease: mechanisms and therapeutic prospects - Yan, Ruyu; Feng, Hongfang; Zhang, Jie (Frontiers in Immunology, 2026)
Parkinson’s disease (PD) is characterized by the progressive loss of dopaminergic neurons, with growing evidence underscoring the critical role of immunosenescence—the age-related dysregulation of the immune system—in its pathogenesis. This review delineates the intricate interplay between systemic immunosenescence, chronic neuroinflammation, and neurodegeneration in PD. We explore how age-related remodeling of the peripheral immune system, termed “inflammaging,” promotes a pro-inflammatory milieu that compromises blood-brain barrier integrity and drives microglial activation within the central nervous system. A central focus is the senescence-associated secretory phenotype, a cocktail of pro-inflammatory factors released by senescent glial cells, which perpetuates a self-sustaining cycle of neuroinflammation, facilitates the propagation of pathological α-synuclein, and ultimately accelerates neuronal loss. The review further examines the disruption of vital neuroimmune communication pathways, including aberrant neuron-glia and gut-brain axis signaling, which are corrupted in the aging brain. We evaluate the translational promise of emerging therapeutic strategies designed to target this immunosenescence-neuroinflammation axis. These include senolytic agents to clear senescent cells, adoptive regulatory T-cell therapy, cytokine-targeted immunomodulation, and immune rejuvenation approaches. Finally, we discuss significant translational challenges and outline future research directions, emphasizing the need for advanced model systems, biomarker development, and AI-driven personalized medicine to successfully develop disease-modifying immunotherapies that disrupt the vicious cycle of immunosenescence and neurodegeneration in PD.